2021
DOI: 10.3389/fmolb.2021.740650
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dissection of Pro-Fibrotic IL11 Signaling in Cardiac and Pulmonary Fibroblasts

Abstract: In fibroblasts, TGFβ1 stimulates IL11 upregulation that leads to an autocrine loop of IL11-dependent pro-fibrotic protein translation. The signaling pathways downstream of IL11, which acts via IL6ST, are contentious with both STAT3 and ERK implicated. Here we dissect IL11 signaling in fibroblasts and study IL11-dependent protein synthesis pathways in the context of approved anti-fibrotic drug mechanisms of action. We show that IL11-induced ERK activation drives fibrogenesis and while STAT3 phosphorylation (pST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 38 publications
3
56
0
Order By: Relevance
“…We have shown previously that TGFβ1 or IL11 stimulation of human cardiac fibroblasts over a 24 h time course causes disparate p-STAT3 profiles but common biphasic activation of ERK (Widjaja et al, 2021a). We examined whether this pattern was linked with phosphorylation of LKB1 (p-S428; putative inactive LKB1), AMPK (p-T172; active AMPK) or mTOR (S2448; active mTOR) ( Figure 1A and S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown previously that TGFβ1 or IL11 stimulation of human cardiac fibroblasts over a 24 h time course causes disparate p-STAT3 profiles but common biphasic activation of ERK (Widjaja et al, 2021a). We examined whether this pattern was linked with phosphorylation of LKB1 (p-S428; putative inactive LKB1), AMPK (p-T172; active AMPK) or mTOR (S2448; active mTOR) ( Figure 1A and S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…All cells were grown and maintained at 37°C and 5% CO 2 . The culture of primary human cardiac fibroblasts (HCFs), primary human hepatic stellate cells (HSCs), and primary human hepatocytes were described previously (Widjaja et al, 2019(Widjaja et al, , 2021a. Human lung epithelial carcinoma cell line (A549; CCL-185, ATCC) were grown and maintained in DMEM complete medium which contains 10% FBS (10500064, Gibco) and 1% P/S (15140122, Gibco).…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…STAT3 activity has been implicated in proteotoxicity due to overloading of the endoplasmic reticulum. It has been demonstrated that Stattic prevented IL-11-induced fibrogenesis by inhibiting both ERK and STAT3 (53).…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 activity has been implicated in proteotoxicity due to overloading of the endoplasmic reticulum. It has been demonstrated that Stattic prevented IL-11-induced fibrogenesis by inhibiting both ERK and STAT3 ( 53 ). The extent to which STAT3 and ERK interact under IL-11 stimulation in OFs is currently being investigated.…”
Section: Discussionmentioning
confidence: 99%